Injeção de nanoferro (nZVI) para remediação de solo argiloso contaminado com cromo hexavalente - Siveris, Wagner Luis (2018)
The anthropic action on the environment is increasingly present currently. Various chemicals daily are bestowed by the anthropic action in soils causing contamination and, in turn, triggering problems for public health and the environment. In this way, it is necessary the application of techniques for the remediation of contaminated areas with the aim of reducing this contamination to acceptable levels by legislation. There are many existing techniques for the remediation and recovery of contaminated areas, among these techniques, the use of nanoparticles of zero valent iron (nZVI) through injection under pressure, is something innovative. Thus, the objective of this work was to evaluate the efficiency of the nZVI injection process for the reduction of hexavalent chromium (Cr 6+) in reduced scale in clay soil. The Chromium has no odor, is very resistant to corrosion and has considerable environmental and geological importance, occurring mainly in the trivalent forms and hexavalent. The effects of chromium are dependent on their state of oxidation, because while the Cr6+ is toxic to be a carcinogenic agent, the Cr3+ is considered an essential nutrient for humans. The research followed the following steps: mounting of the equipment, collection of soil, soil contamination, assembly of the bodies of evidence, pilot testing, application of the injection technique and evaluation of the influence of the injection process in the reduction of hexavalent chromium present in the soil. For conducting the tests, were molded deformed bodies of evidence with 250 mm in height and 335 mm in diameter. The bodies of evidence were contaminated with hexavalent chromium (Cr 6+) at a concentration of 100 mg/kg. The injections under pressure of nZVI, passed through evaluation of parameters of pressure, concentration of nZVI and speed of ascent of the rod, to be determined to better efficiency of the remediation process, taking as excellent values obtained from pressure,concentration and speed of ascent of the rod, 600 kPa, 12.5 g/kg and 12,5 cm/min respectively. It was evaluated the influence of moisture and pH in three rays and three pre-determined depths and held the quantification of the contaminant residual content over the experiment time. It was concluded that the injection system was efficient for the soil remediation process, once there was a homogeneity in the dispersion of nZVI suspension and overall contaminant reduction to the end of the experiment, showing an injection process efficiency of approximately 91.4%